Methodological Aspects of Innovation Statistics and the Innovativeness of Latvia - Jesiļevska, Svetlana (Lithuanian Journal of Statistics, 2012)
The target of this paper is to illustrate the statistical methodology used for collecting and presentating data thatcharacterizes innovation processes in Latvia, and to show the main empirical results of innovativeness in Latvia. For thispurpose, a literature review, as well as statistical analysis methods such as grouping, processing and comparison methods areused. The Central Statistical Bureau of Latvia (CSB) collects data on innovation activities within business enterprises in Latvia on a regular basis, using a methodology supplied by Eurostat. Measuring Innovation is a major step towards evidencebasedinnovation policy making. This paper presents the experience of the Central Statistical Bureau of Latvia whencollecting and presenting data on innovativeness in Latvia and gives some proposals to improve co-operation betweenstatisticians and respondents and to motivate enterprises to provide correct and accurate data on innovations. The empiricalresults of CIS 2010 presented in this paper are based on a sample of 1358 enterprises.
Keywords: linkages in the innovation process; Community Innovation Survey; innovative enterprises; statistics on patents; methodological recommendations